Prediction of concrete fatigue durability using Bayesian neural networks - Słoński, Marek (Computer Assisted Methods in Engineering and Science; Vol 12 No 2-3 (2005), 2022)
The utility of Bayesian neural networks to predict concrete fatigue durability as a function of concrete mechanical parameters of a specimen and characteristics of the loading cycle is investigated. Bayesian approach to learning neural networks allows automatic control of the complexity of the non-linear model, calculation of error bars and automatic determination of the relevance of various input variables. Comparative results on experimental data set show that Bayesian neural network works well.